Grotesque and Performance in the Art of Aubrey Beardsley - STEAD, Evanghelia (Open Book Publishers, 2024)
“If I am not grotesque, I am nothing.” This insightful study illuminates previously unexplored aspects of Aubrey Beardsley’s relationship to the grotesque and his use of media, particularly his manipulation of the periodical press. For the first time and with keen intelligence, Evanghelia Stead fully reveals the aesthetic importance of Beardsley’s Bon-Mots vignettes, as well as the relationship between Darwinism, his innovative foetus motif, and Decadence itself. Beautifully illustrated throughout, the book calls on histories of culture and aesthetics to show how the artist reworked traditional imagery and manipulated it beyond recognition—revealing for instance the influence of cathedral grotesques on Beardsley’s own grotesque performances. Stead also demonstrates his major impact on Italian, French, American and German creative minds through the periodical press. Rich in original thought and detailed, comparative analysis, this book is an invigorating and enlightening read for scholars of Aubrey Beardsley, as well as for anyone interested in nineteenth-century visual culture, art history, art criticism, print culture, illustration, grotesque iconography, and cultural history.